Factors dominating 3-dimensional ozone distribution during high tropospheric ozone period. (January 2018) - Chen, Xiaoyang; Liu, Yiming; Lai, Anqi; Han, Shuangshuang; Fan, Qi; Wang, Xuemei; Ling, Zhenhao; Huang, Fuxiang; Fan, Shaojia
Abstract: Data from an in situ monitoring network and five ozone sondes are analysed during August of 2012, and a high tropospheric ozone episode is observed around the 8th of AUG. The Community Multi-scale Air Quality (CMAQ) model and its process analysis tool were used to study factors and mechanisms for high ozone mixing ratio at different levels of ozone vertical profiles. A sensitive scenario without chemical initial and boundary conditions (ICBCs) from MOZART4-GEOS5 was applied to study the impact of stratosphere-troposphere exchange (STE) on vertical ozone. The simulation results indicated that the first high ozone peak near the tropopause was dominated by STE. Results from process analysis showed that: in the urban area, the second peak at approximately 2 km above ground height was mainly caused by local photochemical production. The third peak (near surface) was mainly caused by the upwind transportation from the suburban/rural areas; in the suburban/rural areas, local photochemical production of ozone dominated the high ozone mixing ratio from the surface to approximately 3 km height. Furthermore, the capability of indicators to distinguish O3 -precursor sensitivity along the vertical O3 profiles was investigated. Two sensitive scenarios, which had cut 30% anthropogenic NOX or VOC emissions, showed that O3 -precursor indicators, specifically the ratios of O3 /NOy, H2 O2 /HNO3 or H2 O2 /NOZ, could partly distinguish the O3 -precursor sensitivity between VOCs-sensitive and NOx-sensitive along the vertical profiles. In urban area, the O3 -precursor relationship transferred from VOCs-sensitive within the boundary layer to NOx-sensitive at approximately 1–3 km above ground height, further confirming the dominant roles of transportation and photochemical production in high O3 peaks at the near-ground layer and 2 km above ground height, respectively. Graphical abstract: Highlights: Three-dimensional ozone was analyzed during a high tropospheric ozone period. Contribution of chemical reactions to O3 differs from urban to non-urban areas. Stratosphere-troposphere exchange induces the high ozone peak near tropopause. Adaptability of O3 -precursor sensitivity in vertical direction are demonstrated. A transition zone of O3 -precursor sensitivity is found at 1–3 km above urban area. Abstract : Distribution and formation mechanism of 3-dimensional ozone in urban/suburban/rural areas. Applications of O3 -precursor sensitivity and its indicators in the vertical direction.